GOVERNANCE AND COORDINATION IN THE BEEF CHAIN: FOCUS ON THE SOUTH-WEST OF BUENOS AIRES (Costos y Gestión, 2021)
The present research addresses the issue of analyzing institutional aspects of livestock in the southwest ofBuenos Aires Province as an interorganizational network by identifying relevant actors of the organizationalfield, and the type of links they maintain, while considering the degree of concentration within the primarylinks and industry where the economic power of small and medium producers is observed. Likewise, thiswork seeks to understand the dynamics of the transactions carried out by the actors within the chain bydetermining the dimensions which characterize them, and the governance mechanisms that emerge fromthem. In this way, the aim is to complement the approaches traditionally applied to the study of agribusinessin order to consider other actors and links based on normative, cultural or cognitive aspects, which conditionthe behavior of agents.Initially, a mapping of the organizational field is carried out which manifests its complexity because of thediversity of actors involved and the type of relations they maintain with each other. The configuration of theinter-organizational networks that make up the field presents certain stability in the links, which would favora rapid diffusion of information and knowledge if the number of ties between the agents was increased.This stage identifies the most relevant actors within each link in the chain, which are considered to analyzepressure from the institutions and factors that influence the coordination or governance mechanisms thatthe chain adopts. As regards the pressure from institutions affecting agribusiness, they are mostly of coerciveand normative origin – the former as a consequence of dependency of access to critical resources, and thelatter from the action of professional advisers. As regards the governance of the chain, a modality through themarket is inferred, with a tendency towards a modular or even relational structure, as a result of the demandsof the international market.This work enriches the academic-scientific field by providing a conceptual framework that integrates the theoreticalapproaches belonging to the administration field, which are generally independently applied on thestudy of agribusiness, from a perspective of complementarity.
Keywords: neo-institutional approach; global value chain; cattle breeding; interorganizational network; south-west buenos aires province, Argentina